2020
DOI: 10.1016/j.heliyon.2020.e04970
|View full text |Cite
|
Sign up to set email alerts
|

Integrating endemic medicinal plants into the global value chains: the ecological degradation challenges and opportunities

Abstract: Though innovations for sustainable management of natural resources have emerged over time, the rising demand for nature based health solutions and integration of endemic flora into global value chains could have adverse impacts on ecosystems. The ecological risks in the exploitation of the wild endemic medicinal plant resources are exacerbated by a myriad of agrotechnological risks and challenges that highly constrain their domestication. Successful exploitation and commercialisation of medicinal plants thus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…The global trade of medicinal plants and their derivatives was estimated at 33 billion USD in 2014, and the World Health Organization (WHO) has estimated that this will increase to 50 trillion USD by 2050. The export of medicinal plants in China increased eight-fold from 2010 to 2015 ( Pyakurel et al, 2018 ; Volenzo and Odiyo, 2020 ). Traditional Chinese medicines not only occupy an important position in the global medical field but are also used in dietary supplements, food, and other products ( Yao et al, 2018 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The global trade of medicinal plants and their derivatives was estimated at 33 billion USD in 2014, and the World Health Organization (WHO) has estimated that this will increase to 50 trillion USD by 2050. The export of medicinal plants in China increased eight-fold from 2010 to 2015 ( Pyakurel et al, 2018 ; Volenzo and Odiyo, 2020 ). Traditional Chinese medicines not only occupy an important position in the global medical field but are also used in dietary supplements, food, and other products ( Yao et al, 2018 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…They also opined that cultivation of medicinal plants could contribute to the economic empowerment of women in rural areas. However, Volenzo and Odiyo (2020) pointed to the low benefits for growers of medicinal plants even in the face of increasing international trade, and attributed this to existing non-tariff barriers -such as health and safety requirements, and high transactional costs. Ndou et al (2019) investigated the medicinal plants value-chain in South Africa, and identified the various actors involved in the sector.…”
Section: Related Studies On Cultivation Of Medicinal Plants In South Africamentioning
confidence: 99%
“…However, very few studies have explored the challenges of medicinal plants cultivation and commercialization among smallholder producers. There are myriad of risks and challenges inherent in the domestication of medicinal plants, which Volenzo and Odiyo (2020) claimed to require additional comprehension. Astutik et al (2019) considered this an amplification of the need for empirical investigation of medicinal plants production systems.…”
Section: Introductionmentioning
confidence: 99%
“…The increased population led to a higher utilization of these plants, so their residues are proportional, with a huge amount of biomass generated as by-products [ 6 ], representing a growing market in the natural-based products [ 7 ]. The general use of MAPs all over the world is not homogenic, due to different factors: (i) in developed countries, even if the demand for natural treatments is high, profits of the growers and producers remain low because of the existing intermediaries which increase the price, as well as the lack of organization and networking by the poor collectors of medicinal plants from the wild; (ii) rigorous regulations and documentations requirements; and (iii) in less developed countries, there are poor traceability mechanisms from plant to population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%